Do macroprudential measures increase inequality? Evidence from the euro area household survey - Oana-Maria Georgescu; Diego Vila Martin (European Central Bank (ECB), 2021)
Borrower-based macroprudential (MP) policies - such as caps on loan-to-value (LTV) ratios and debt-service-to-income (DSTI) limits - contain the build-up of systemic risk by reducing the probability and conditional impact of a crisis. While LTV/DSTI limits can increase inequality at introduction, they can dampen the increase in inequality under adverse macroeconomic conditions. The relative size of these opposing effects is an empirical question. We conduct counterfactual simulations under different macroeconomic and macroprudential policy scenarios using granular income and wealth data from the Households Finance and Consumption Survey (HFCS) for Ireland, Italy, Netherlands and Portugal. Simulation results show that borrower-based measures have a moderate negative welfare impact in terms of wealth inequality and a negligible impact on income inequality.
Keywords: G21; G28; G51; 330; macroprudential policy; inequality; household debt